PENGARUH VARIASI MASSA ROLLER DAN UKURAN V-BELT CVT TERHADAP DAYA DAN TORSI MOTOR MATIC 125 CC: THE EFFECT OF VARIATION OF ROLLER MASS AND V-BELT SIZE CVT ON POWER AND TORQUE MOTOR MATIC 125 CC - Abrar Sinatrya Cahyacerananda, Abrar Sinatrya Cahyacerananda (Jurnal Teknik Mesin, 2022)
The purpose of this study was to analyze the results of the power and torque produced by 125 cc motorcycles in 2014 using variations in roller mass and v-belt size. The study method used is experimental study method. The results of the study using v-belt variation 1 obtained the highest power and torque for the 8 gram roller at 9.93 HP, for the 10 gram roller at 9.16 HP, while for the 12 gram roller at 8.36 HP at 3500 rpm. The highest torque by the 8 gram roller reaches 24.05 N.m. The 10 gram roller reaches 27.67 N.m, while the 12 gram roller reaches 26.19 N.m at 1500 rpm. The highest power and torque using the v-belt variation 2 is produced by the 8 gram roller at 9.7 HP, for the 10 gram roller at 9.23 HP, while the 12 gram roller is at 9 HP, at 5500 rpm. The 8 gram roller's highest torque reaches 25.9 N.m. For a 10 gram roller it reaches 23.41 N.m, while a 12 gram roller reaches 24.31 N.m